How should the long-term investor harvest variance risk premiums? - Julian Dörries; Olaf Korn; Gabriel J. Power (University of Cologne, Centre for Financial Research (CFR), 2023)
Derivatives strategies that aim to earn variance risk premiums are exposed to sharp price declines during market crises, calling into question their suitability for the longterm investor. Our paper defines, analyzes, and proposes potential solutions to three problems (payoff, leverage and finite maturity) linked to designing suitable variancebased investment strategies. We conduct an empirical study of such strategies for the S&P 500 index options market and find strong effects of certain design elements on risk and return. Overall, our results show that variance strategies can be attractive to the long-term investor if properly designed.
Keywords: G10; G11; G23; 330; Variance Risk Premium; Variance Factor; Trading Strategies; Long-term Investor